Características reprodutivas dos seis aos 36 meses de idade de machos da raça Guzerá criados a pasto na região do cerrado mineiro - Jair Perez Osorio (2010)
The aims of this study were to characterize some reproductive traits of young males in order to subsidize evaluation and selection of sires of the Guzerat breed and to evaluate the correlation between scrotal circumference (SC) and volume (VL). A total of 1,757 observations on 330 Guzerat males, aging from 6 to 36 month, were performed. SC, length and width of both testis were measured and VL was estimated according to Fields et al., 1979. Growth curves for SC and VL reached inflection points, respectively, at 13,21 (18.1 cm) and 23.3 months of age (389.4 cm3). The growth rates of SC and VL, before and after the inflection point, were 0.58 cm/mo, 16.3 cm3/mo, 0.29 cm/mo, 7.7 cm3/month of age, respectively. Direction and strength of correlation between SC and VL (0.91; P<0.001). Related to testicular morphology the testicular forms long / moderate (n = 479) which represent 53.7%, and the long/oval forms (n = 348) 39.1% had been the testicular forms of higher frequency of cases in this study. The results indicated that in Guzerat breed the scrotal circumference estimate efficiently the scrotal volume, because of its high correlation to the use of scrotal circumference and recommended for selection of breeding programs, this method would be easier, efficient and quick to use for choosing of animals with greater precocity